Categorização do shuttle walk test e do SF-36 de acordo com os qualificadores da classificação internacional de funcionalidade, incapacidade e saúde: proposta de utilização em pacientes com Diabetes Mellitus tipo 2 - Silva, Conceição Aparecida Vitoriano Souza (2023)
Introduction: The prevalence of type 2 Diabetes Mellitus (DM2) has increased substantially over the years, and the impact generated by the delay in public awareness and the consequences generated in society and the economy, lead to the need to improve the view of disability and functionality, since assessing, monitoring and classifying functionality according to different perspectives are important to successfully develop truly effective interventions, targeting each individual. Objective: To categorize the results of the Incremental Shuttle Walk Test (ISWT) and the Short Form Health Survey (SF-36) with the qualifiers of the International Classification of Functioning, Disability and Health (ICF) in the population with type 2 diabetes mellitus. Method: This was a retrospective study of 48 individuals with DM2, using the Incremental Shuttle Walk Test and the SF- 36 questionnaire as assessment methods. To qualify the results, we analyzed the percentage of distance walked in relation to the percentage predicted (Study 1) and the total SF-36 score (Study 2). Body mass index (BMI) and physical activity level (IPAQ) were also analyzed. Results: Study 1: Among the forty-eight individuals, eight (16.6%) had a mild problem, 27 (56.3%) had a moderate problem and 13 (27.1%) were classified as having a severe problem. No participant was classified as having a complete problem or no functional capacity problems. Study 2: Among the forty-eight individuals, 14 (29.16%) had a mild problem, 21 (43.75%) had a moderate problem and 13 (27.08%) were classified as having a severe problem. No participant was classified as a complete problem or without problems in relation to the total SF36 score. Conclusion: Study 1: The ICF qualifiers were able to categorize the ISWT and classified the limitation of functional capacity into mild, moderate, and severe. It therefore proved to be a useful clinical tool for assessment, monitoring, and clinical decision-making. Study 2: The ICF qualifiers were able to classify health-related quality of life and proved to be a useful clinical tool for assessment, follow-up, and clinical decision- making.